The greatest contribution to medical science is the transformation from studying symptoms to studying their causes—the unrelenting legacy of Robert Koch and Louis Pasteur—and a causality perspective to approach a definition of SLE - Rekvig, Ole Petter (Frontiers in Immunology, 2024)
The basic initiative related to this study derives from the fact that SLE is a unique and fertile system science object. We are, however still far from understanding its nature. It may be fair to indicate that we are spending more time and resources on studying the complexity of classified SLE than to study the validity of classification criteria. This study represents a theoretical analysis of current instinctual SLE classification criteria based on “The causality principle”. The discussion has its basis in the radical scientific traditions introduced by Robert Koch and Louis Pasteur. They announced significant changes in our thinking of disease etiology by implementation of the modern version of “The Causality Principle”. They influenced all aspects of today´s medical concepts and research: Transformation of medical science from studies of symptoms to study their causes, relevant for mono-symptomatic diseases as for syndromes. Their studies focused on bacteria as causes for infectious diseases, and on how the immune system adapts to control and prevent contagious spreading. This is the most significant paradigm shift in modern history of medicine, and resulted in radical changes in our view on the immune system. They described acquired post infection immunity and active immunization by antigen-specific vaccines. The paradigm “transformation” has great theoretical impact also on current studies of autoimmune diseases like SLE: Symptoms and their cause(s). In this study, evolution of SLE classification and diagnostic criteria is discussed in “The Causality Principle” perspective, and if contemporary SLE classification criteria are as useful as believed today for SLE research. This skepticism is based on the fact that classification criteria are not selected based on cogent causal strategies. SLE classification criteria do not harmonize with Koch´s and Pasteur´s causality principle paradigms, and not with Witebsky´s Koch-derived postulates for autoimmune and infectious diseases. It is not established whether classification criteria can separate SLE as a “one disease entity” from “SLE-like non-SLE disorders” - the latter in terms of SLE imitations. This is discussed here in terms of weight, rank, and impact of classification criteria: Do they all originate from “one basic causal etiology”? Probably not.